Społeczne koszty wdrażania ideologii gender - Monika Kacprzak (Colloquia Theologica Ottoniana, 2014)
The theory of gender, growing in the social sciences since the mid- twentieth century, grew more than academic discourse becoming a political category. By supporters is presented as a tool to combat violence against women and to implement the principle of gender equality at all levels of existence. Analysis of the key demands of gender using, developed by Robert Putnam and Francis Fukuyama, theory of social capital leads to different conclusions. The purpose of this article is to present some of the costs incurred by society as a result of the implementation of the demands of gender in political programs, economic and educational. This paper presents the most important criteria of this theory, the analysis from the perspective of sociological, anthropological and Catholic apology against major assumptions.